Ground state properties of CeNi12B6. (18th March 2015) - Michor, H; Markota, T; Messner, I M; Özcan, S; Schwarzböck, F; Salamakha, L; Tako, Z S; Bauer, E; Sologub, O
Abstract: We report on the ground state features of the orthorhombic ternary compound CeNi12 B6 which exhibits a large Ce-Ce interatomic distance of 6.07 Å. Magnetic and electronic properties were studied by means of low temperature heat capacity and electrical resistivity measurements performed down to 0.4 K, high pressure resistivity studies and by magnetic susceptibility measurements. The low temperature heat capacity reveals a sharp second order type antiferromagnetic phase transition at TN = 1.85 K with an entropy gain of only 0.3 R ln2 at TN . The initial temperature dependence of the heat capacity as well as resistivity data is well accounted for by a model for gapped antiferromagnetic magnons yielding an exceptionally large spin wave excitation gap Δ ~ 2.2 TN . Single crystal magnetic susceptibility studies reveal a huge uni-axial single-ion crystal field anisotropy confining the moments along the orthorhombic c -axis. The application of quasi-hydrostatic pressure up to 1.4 GPa causes an increase of the Néel temperature to 2.3 K at 1.4 GPa.